2003
DOI: 10.3354/dao055125
|View full text |Cite
|
Sign up to set email alerts
|

nfection patterns ofMyxobolus heterosporain two tilapia species (Teleostei: Cichlidae) and its potential effects

Abstract: A Myxobolus heterospora (Baker, 1963) infection was found in 2 euryhaline tilapia species, Sarotherodon melanotheron melanotheron (Rüppel, 1853) and Tilapia zillii (Gervais, 1852), from a brackish water lake, Lake Nokoué (Benin, West Africa). The histology and ultrastructure of different levels of infection in intestinal connective tissues and wall tissues is described. A total of 391 S. melanotheron melanotheron and 222 T. zillii were examined from October 1987 to October 1989. M. heterospora was found thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…nov. This finding is in agreement with accounts describing some Myxozoa species (Gbankoto et al 2001, Viozzi & Flores 2003, but contrasts with others (Muzzall 1995, Gbankoto et al 2003 that reported a significant difference between females and males regarding the prevalence of infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…nov. This finding is in agreement with accounts describing some Myxozoa species (Gbankoto et al 2001, Viozzi & Flores 2003, but contrasts with others (Muzzall 1995, Gbankoto et al 2003 that reported a significant difference between females and males regarding the prevalence of infection.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in contrast to results described by Gbankoto et al (2001), who report the occurrence of significant seasonal variations in Myxobolus sp. and Myxobolus zillii parasites of Sarotherodon melanotheron melanotheron and Tilapia zillii, respectively, and Gbankoto et al (2003), who report seasonal differences in the infection of S. melanotheron melanotheron by Myxobolus heterospora. However, the results of the present study are in agreement with those described by Gbankoto et al (2003), who report no seasonal variation in the infection of T. zillii by M. heterospora.…”
Section: Discussionmentioning
confidence: 96%
“…The infection pattern with a peak at a particular age and size host and a subsequent decrease in older animals, a convex profile, has also been described for fish myxosporeans (2,21,34,43) and some fish protozoans (37). Biological, ecological, and immunological aspects may affect the host age distribution and dispersion patterns.…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have described similar findings (Gbankoto et al 2001;Viozzi and Flores 2003;Milanin et al 2010). However, other authors have reported significant difference between females and males regarding the prevalence of infection (Muzzall 1995;Gbankoto et al 2003).…”
Section: Discussionmentioning
confidence: 89%